Pengenalan Tumbuhan Yang Berpotensi Sebagai Obat Pada Ibu-Ibu PKK RT 004 Kelurahan Labuhan Ratu Bandar Lampung - Yulianty; E Nur Azizah; Nida Lidya Susanti; Tuti Yuliani (CV. Multi Kreasi Media, 2025)
Community service with the theme Introduction of Plants that have Potential as Medicine is carried out with the aim of introducing plants that can be used as medicine. These plants can be collected and planted on a large or narrow yard. The existence of land specifically used to plant medicinal plants is an effort to preserve medicinal plants. These plants can be utilized by the community in Labuhan Ratu Village, especially the women of PKK RT 004 Labuhan Ratu Bnadar Lampung. This activity includes socialization of the importance of preserving plants that have potential as medicine. The evaluation results showed an increase in knowledge about medicinal plants. The average pre-test score was 76.15 points and the average post-test score increased to 92.31 points. The sustainability of this activity needs to be done so that a TOGA Garden can be formed in RT 004 Labuhan Ratu Bandar Lampung.